Ethical Concerns About Human Genetic Enhancement in the Malay Science Fiction Novels - Isa, Noor Munirah; Safian Shuri, Muhammad Fakhruddin (Springer Verlag, 2018)
Advancements in science and technology have not only brought hope to humankind to produce disease-free offspring, but also offer possibilities to genetically enhance the next generation’s traits and capacities. Human genetic enhancement, however, raises complex ethical questions, such as to what extent should it be allowed? It has been a great challenge for humankind to develop robust ethical guidelines for human genetic enhancement that address both public concerns and needs. We believe that research about public concerns is necessary prior to developing such guidelines, yet the issues have not been thoroughly investigated in many countries, including Malaysia. Since the novel often functions as a medium for the public to express their concerns, this paper explores ethical concerns about human genetic enhancement expressed in four Malay science fiction novels namely Klon, Leksikon Ledang, Transgenesis Bisikan Rimba and Transgenik Sifar. Religion has a strong influence on the worldview of the Malays therefore some concerns such as playing God are obviously religious. Association of the negative image of scientists as well as the private research companies with the research on human genetic enhancement reflects the authors’ concerns about the main motivations for conducting such research and the extent to which such research will benefit society.